Improvement of symptoms in a rat model of depression through combined zinc and folic acid administration via up-regulation of the Trk B and NMDA. (14th September 2018) - Dou, Mei; Gong, Anjing; Liang, Hui; Wang, Qiuzhen; Wu, Yanyan; Ma, Aiguo; Han, Lei
Highlights: Combined administration of zinc and folic acid can improve the symptoms of depression-model rats. The mechanism of the effects of combined zinc and folic acid on depression-model rats is related to increased levels of 5-HT, DA and NE in the brain. The mechanism of the effects of combined zinc and folic acid on depression-model rats is also related to to the up-regulation of Trk B and NMDA. Abstract: The aim of this study was to observe the influence of combined zinc and folic acid administration on depression and to explore its mechanism of action. Male Sprague Dawley rats were randomly divided into five groups: control, model, paroxetine (P), zinc + folic acid (ZnY), and zinc + folic acid + paroxetine (ZnYP) groups. Rat models of depression were established by chronic mild unpredictable stress for three weeks. These rats were then treated with different interventions for four weeks and the sucrose preference test was then performed to observe changes in rats' behavior. An HPLC-electrochemical method was used to detect the levels of 5-hydroxytryptamine (5-HT), dopamine (DA) and norepinephrine (NE) in the frontal cortex. qRT-PCR was employed to detect the mRNA levels of tyrosine kinase receptor B (Trk B) and N-methyl-D-aspartate acid (NMDA) in the frontal cortex; Western blotting was used to detect the protein levels of brain derived neurotrophic factor (BDNF) in the frontal cortex. The results showed that compared with the model group, sucrose consumption, 5-HT, NE and DA levels were significantly increased in the ZnY group ( P  < 0.05). Also the mRNA levels of Trk B and NMDA were significantly increased in the ZnY group compared with the model group ( P  < 0.001). No significant up-regulation of BDNF was observed in the ZnY group. We conclude that combined administration of zinc and folic acid can improve the symptoms of depression-model rats, and its mechanism is related to increased levels of 5-HT, DA and NE in the brain, and to the up-regulation of Trk B and NMDA.